Environmental sanitation and its relationship with the prevalence of intestinal parasites - Jennifer Gotera; Amelia Panunzio; Ayari Ávila; Francis Villarroel; Octoban Urdaneta; Belkis Fuentes; Johan Linares (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2019)
Intestinal parasites are considered an important public health problem. The purpose of the research was to relate environmental sanitation to the prevalence of intestinal parasites in three urban communities of the Maracaibo municipality. Type of descriptive, correlational, cross-sectional research. The identification of risk factors for environmental sanitation was made through an epidemiological sheet, involving a total of 345 individuals, including as variables to investigate the sanitation: water storage, accumulation of garbage, presence of harmful fauna and overcrowding in housing. For the identification of intestinal parasites, a direct coproparasitological examination was performed with physiological saline solution and lugol. Statistical analyzes were performed applying frequency distributions, contingency tables and association of variables using the Chi square test, applying the SPSS V.20. Regarding the main risk factors of environmental sanitation, it was found: water storage (98%), garbage accumulation (94%) and presence of harmful fauna (92%). The prevalence of parasitosis was 46%, mainly by Blastocystis sp (72%), resulting in 65% monoparasitic. 48% presented inadequate environmental sanitation, 39% of the sample presented parasitosis when there is poor environmental sanitation. In conclusion, it was found that the prevalence of parasitic infections was high, as well as the associated risk factors, which led to an association between inadequate environmental sanitation and the presence of parasitosis in the studied communities.